Evaluation of the Efficacy and Safety of Topical Imiquimod 5% for Plaque-Type Morphea: A Multicenter, Prospective, Vehicle-Controlled Trial. Issue 2 (March 2015) - Dytoc, Marlene; Wat, Heidi; Cheung-Lee, Melody; Sawyer, Douglas; Ackerman, Thomas; Fiorillo, Loretta
Background: There is currently a lack of evidence-based therapies that are safe and effective for plaque-type morphea. We aimed to evaluate the therapeutic potential and safety profile of imiquimod 5% cream in plaque-type morphea. Methods: We enrolled 25 adult patients from two Canadian centers with histologically confirmed plaque-type morphea. Imiquimod 5% was applied to a representative plaque, and vehicle was applied to a control plaque for 9 months. Treatment efficacy was assessed with the Dyspigmentation, Induration, Erythema, and Telangiectasias (DIET) score, histology, and ultrasound evaluation. Results and Conclusions: Twenty-two patients completed the entire length of the study. Imiquimod 5% was superior to vehicle in reducing DIET scores at 3, 6, 9, and 12 months ( p < .05). Induration demonstrated the greatest response. Histologic evaluation showed significant improvement or resolution of disease. However, no ultrasonographic differences were found in dermal and hypodermal thicknesses between the treatment and vehicle groups ( p > .05). Adverse effects were minimal and well tolerated.